2010
DOI: 10.4049/jimmunol.0901929
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Wound Healing in Mice with Deficiency of IL-6 versus IL-6 Receptor

Abstract: IL-6 modulates immune responses and is essential for timely wound healing. As the functions mediated by IL-6 require binding to its specific receptor, IL-6Rα, it was expected that mice lacking IL-6Rα would have the same phenotype as IL-6–deficient mice. However, although IL-6Rα–deficient mice share many of the inflammatory deficits seen in IL-6–deficient mice, they do not display the delay in wound healing. Surprisingly, mice with a combined deficit of IL-6 and IL-6Rα, or IL-6–deficient mice treated with an IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
177
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(187 citation statements)
references
References 66 publications
6
177
2
Order By: Relevance
“…ADAM10, or even an entirely different mechanism is responsible for serum sIL-6R generation. Here, we show that conditional ablation of ADAM10 in myeloid cells, which have been reported to generate the bulk (63%) of blood-borne sIL-6R (18), also resulted in unaltered sIL-6R serum levels. We further excluded neutrophil elastase, cathepsin G, and proteinase 3, which are highly abundant in myeloid cells, from contributing to sIL-6R generation in mouse as well as human blood.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…ADAM10, or even an entirely different mechanism is responsible for serum sIL-6R generation. Here, we show that conditional ablation of ADAM10 in myeloid cells, which have been reported to generate the bulk (63%) of blood-borne sIL-6R (18), also resulted in unaltered sIL-6R serum levels. We further excluded neutrophil elastase, cathepsin G, and proteinase 3, which are highly abundant in myeloid cells, from contributing to sIL-6R generation in mouse as well as human blood.…”
mentioning
confidence: 94%
“…cDNA was synthesized from 1 g of RNA with RevertAid TM Moloney MuLV reverse transcriptase (Fermentas, Thermo Scientific) using oligo(dT) 18 primer. Murine IL-6R mRNA transcripts were amplified via PCR using the following primers: mu IL-6R forward 1, 5Ј-AAG GAG GAG CTT GAC CTT GG-3Ј (Exon 6); mu IL-6R reverse 1, 5Ј-GTG GAG GAG AGG TCG TCT TG-3Ј (Exon 10); mu IL-6R forward 5UTR, 5Ј-GTG CGA GCT GAG TGT GGA G-3Ј; mu IL-6R forward Exon1, 5Ј-GGC TGC ACG CTG TTG GTC-3Ј; and mu IL-6R forward Exon4, 5Ј-ACA GTG TGG GAA GCA AGT CC-3Ј.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…IL6 can display pro‐ and anti‐inflammatory actions: IL6‐KO mice exhibit impaired granulation tissue formation and delayed cutaneous wound healing; IL6‐KO dermal fibroblasts had decreased production of matrix enzymes, suggesting an IL6 role in modulating fibroblast function (Luckett & Gallucci, 2007). One later study demonstrated that IL6Rα‐ERK signaling improved wound healing (McFarland‐Mancini et al ., 2010). In contrast to IL6, IFN‐γ decreased formation of new granulation tissue in rats and dysregulated collagen production and in vitro experiments demonstrated that IFN‐γ decreased collagen synthesis in rat fibroblasts (Laato et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%